Multiscalar Practices of Fossil Fuel Displacement. Issue 3 (22nd March 2022) - Sareen, Siddharth; Grandin, Jakob; Haarstad, Håvard
Abstract : As renewable energy sources increasingly outcompete fossil fuels on cost and efficiency, novel questions arise around how, when, and where renewables can displace fossil energy. We need to understand fossil fuel displacement as a sociopolitical and spatial process. In this article, we focus particularly on the scales and practices of legitimation through which fossil fuel displacement occurs. We advance an understanding of how such displacement is conditioned by incumbent multiscalar arrangements and of how these can be overcome. We suggest that there are different practices of displacement that operate across multiple scales—here conceptualized as discursive, financial, institutional, and infrastructural—and use them to develop an analysis of solar rollout and fossil phase-out in Portugal. Our analysis shows that although renewables have partially displaced fossil fuels both discursively and financially, they have not yet displaced the historically large-scale nature of energy generation. Rather, the persistence of fossil fuel geographies and sectoral institutional arrangements keeps the displacements of energy transition at a spatial remove from citizens.